Livestock based integrated farming systems Present status and future prospects in North-East Hill Regions - Bharti, P K; Khan, M H (Indian Farming, 2016)
Livestock based integrated farming system has ample scope to improve the livelihood of the resource poor farmers in northeast hill region. The diverse natural resources with special reference to livestock and agriculture sector in this region favour this type of farming system, where output of one system can efficiently be utilized as an important input for the other system. In this type of farming system, there is recycling of organic matter in a better way to minimize the external input cost and thereby maximize the profitability of farms as a whole. Besides the favourable conditions, several constraints and challenges are also there, which need to be rectified by the researcher, extension personnel and effective implementation of the government policies for better livelihood of the poor farmers. The socio-economic conditions of the farmers of this region can be improved through animal husbandry based farming system, which is not only beneficial but also very essential and complementary to the profitable agriculture.